RELEVANSI SISTEM BIOPORI DALAM UPAYA PENANGANANAN DAN PENCEGAHAN BANJIR MELALUI ANALISIS BIBLIOMETRIC - Rochman, Abdul; Sutryani, Heni; Dewi, Astri Kustina; Nurlukman, Adie Dwiyanto; Fadli, Yusuf (Community Services and Social Work Bulletin, 2023)
Increased studies and research regarding the effectiveness of the biopore system in handling and mitigating floods have been carried out and have shown a positive impact on the effectiveness of the system. This research tries to carry out a bibliometric analysis on the topic of biopores and their relationship to flooding. The research method used in this research is a qualitative method with a bibliographic approach. Data analysis was carried out using Vosviewer on 500 articles related to " biopore". The research results show that overall, research on flood problems and the use of biopore as a treatment solution has important implications in efforts to reduce the impact of flooding and create a more sustainable city. Several studies and research provide an initial picture of the potential effectiveness of biopores in flood management. Although specific data may not yet be available to show that biopores are considered as a potential solution in dealing with flooding problems at the local level.